Offshoring of white-collar jobs: Theory and evidence - Artur Klimek (International Journal of Management and Economics, 2021)
Foreign direct investment (FDI) in advanced business services (ABSs), referred to here as the offshoring of white-collar jobs, has become one of the major developments in the operations of multinational corporations (MNCs). However, a specific theoretical approach to this phenomenon has not been adequately defined. In this article, we have two objectives. The first objective is to outline the key elements of the theoretical framework and introduce a simple formal model for business services within MNCs. The second objective is to verify the assumptions of the model in the empirical part. We use the sample of the largest European companies having foreign affiliates. Special attention is paid to Visegrád economies (i.e. Czech Republic, Hungary, Poland, and Slovakia) as host economies. We applied here a multinomial logistic model, which indicates the probability of having an ABS subsidiary taking into consideration the characteristics of MNCs.
Keywords: F21; F23; 650; advanced business services; Europe; foreign direct investment; multinational corporation